PENGEMBANGAN KEPARIWISATAAN BERBASIS PENGUATAN KOMUNITAS PADA WISATA PANTAI TORONIPA KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Muhammad Amrullah; Takwim Takwim (Yayasan Akrab Pekanbaru, 2019)
This study aims to find out Community Empowerment Based Tourism Development in Toronipa Coastal Tourism Konawe Regency, Southeast Sulawesi. This study uses a qualitative approach, and the methods used are interviews, observation, and documentation study The results of this research are to find out what should be done by the Regional Government for the development of tourism in Toronipa Beach, Konawe Regency, Southeast Sulawesi, explored from communication, resources, implementing attitudes and bureaucratic structures. the resource has been implemented and shows a good situation, but in the aspect or dimension of communication, the bureaucratic structure cannot be implemented properly Factors that influence the implementation of tourism development in Toronipa Beach, Kon Regency awe Southeast Sulawesi, is a supporting factor consisting of natural resources, affordability, safety and comfort of tourists and social media technology used for tourism promotion. While the inhibiting factors consist of, local government service factors, limited facilities and infrastructure and supporting facilities for Toronipa beach tourism.